Out-of-hospital noninvasive ventilation: epidemiology, technology and equipment - John Scott Baird; Thyyar M. Ravindranath (MDPI AG, 2012)
Noninvasive ventilation has been utilized successfully in the pre- and out-of-hospital settings for a variety of disorders, including respiratory distress syndrome in neonates, neurologic and pulmonary diseases in infants and children, and heart failure as well as chronic obstructive pulmonary disease in adults. A variety of interfaces as well as mechanical positive pressure devices have been used: simple continuous positive airway pressure devices are available which do not require sophisticated equipment, while a broad spectrum of ventilators have been used to provide bilevel positive airway pressure. Extensive training of transport teams may be important, particularly when utilizing bilevel positive airway pressure in infants and children.